2010
DOI: 10.3109/02713683.2010.519850
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression in Patients with Dry Eye Syndrome

Abstract: Anxiety and depression are correlated with DES, demonstrating that DES is an important public health problem that merits increased attention and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
93
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(113 citation statements)
references
References 23 publications
10
93
1
3
Order By: Relevance
“…This indicates associations between dry eye symptoms, depression, and ADHD. In the present study, the DES group had a high depression score, and this is consistent with results of previous research [5,6,[8][9][10]. However, there has been no study on the association between DES and ADHD, but was attempted in the present study for the first time.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This indicates associations between dry eye symptoms, depression, and ADHD. In the present study, the DES group had a high depression score, and this is consistent with results of previous research [5,6,[8][9][10]. However, there has been no study on the association between DES and ADHD, but was attempted in the present study for the first time.…”
Section: Discussionsupporting
confidence: 82%
“…They also reported that the Dry eye disease group had a significantly higher depression score than the control group. For 89 DES patients and 73 control group subjects, Li et al [6] compared the associations of DES with depression and anxiety through the OSDI, the Self-rating Anxiety Scale (SAS), and Self-rating Depression Scale (SDS) questionnaires. The results showed that the DES group had significantly higher anxiety and depression scores.…”
Section: Introductionmentioning
confidence: 99%
“…However, this result should be interpreted with caution due to the weak or moderate correlations. In our previous work, 28 we found that dry eye patients are more anxious and depressed than those without dry eye. In the psychiatric clinical setting, anxiety and depression disorders are the most common diseases encountered, so they can be identified easily and treated.…”
Section: Discussionmentioning
confidence: 99%
“…Low VFQ-25 scores in patients with DED have been reported in many studies. [23][24][25]27,28 Additionally, several recent studies have shown that patients with DED had impaired mental health, [28][29][30] which might be explained by low subscale scores related to the mental health of these patients in both the SF-8 and VFQ-25 scales.…”
Section: Discussionmentioning
confidence: 99%